A Host–Parasitoid Model for Aspidiotus rigidus (Hemiptera: Diaspididae) and Comperiella calauanica (Hymenoptera: Encyrtidae). Issue 1 (27th October 2018) - Palen, Dave I; Almarinez, Billy J M; Amalin, Divina M; Legaspi, Jesusa Crisostomo; David, Guido
Abstract: The outbreak of the coconut scale insect Aspidiotus rigidus Reyne (Hemiptera: Encyrtidae) posed a serious threat to the coconut industry in the Philippines. In this article, we modeled the interaction between A. rigidus and its parasitoid Comperiella calauanica Barrion, Almarinez, Amalin (Hymenoptera: Encyrtidae) using a system of ordinary differential equations based on a Holling type III functional response. The equilibrium points were determined, and their local stability was examined. Numerical simulations showed that C. calauanica may control the population density of A. rigidus below the economic injury level.